Māori Research Development: a National Challenge - Editors (New Zealand Science Review, 2014)
​The New Zealand Association of Scientists (NZAS) is seriously concerned by comments made by Dr Leonie Pihama on the exclusion of Māori voices from science funding processes in New Zealand.In a statement published on the Te Wharepora Hou blog site [1], Dr Pihama discusses the impact on the Māori research community of the decision to discontinue Centre of Research Excellence (CoRE) funding of ‘Ngā Pae o Te Māramatanga’, the only CoRE that addresses Māori research needs and capability building in the Māori research community.We acknowledge that the Royal Society of New Zealand and the Tertiary EducationCommission have run an open, contestable process. The Association does not want to criticise individual funding decisions, and observes that these decisions have been made in a highly competitive environment after a process of peer review.However, Ngā Pae o Te Māramatanga plays a unique role in New Zealand’s research landscape, and a strong case can be made that its goals are simply incommensurate with any other CoRE to which it might be compared.We also consider that the points made by Dr Pihama about the wider impact of this decision are well made, especially in the context of the National Science Challenges (NSCs). These ten challenges were not selected in a contestable process but rather after a long consultative period.Of serious concern, then, is the claim that ‘MBIE also took a position against ensuring specific Māori input and aspirations in the process’. The process and timeline of consultation throughout the NSCs has caused some concern in the broader scientific community, but it is scandalous that they did not incorporate the views of Māori from an early stage in their development.The President of the NZAS, Dr Nicola Gaston, said ‘The scientific community struggles with diversity, as was highlighted in the case of gender in a recent Herald article [2].That Māori researchers have struggled to be included in the National Science Challenges is a disgrace and an embarrassment’. The NZAS endorses the recommendations made by Dr Pihama, and urges MBIE to give them serious consideration. [1] http://tewhareporahou.wordpress.com/2014/03/06/the-denial-of-maori-researchdevelopment/ [2] http://www.nzherald.co.nz/science/news/article.cfm?c_id=82&objectid=11216759